Prospective randomized open-label trial to evaluate risk faCTor management in patients with unruptured intracranial aneurysms: study protocol - Vergouwen, Mervyn; Rinkel, Gabriel Je; Algra, Ale; Fiehler, Jens; Steinmetz, Helmuth; Vajkoczy, Peter; Rutten, Frans H.; Luntz, Steffen P.; Hänggi, Daniel; Etminan, Nima (International journal of stroke, 2018)
RATIONALE: Unruptured intracranial aneurysms are currently left untreated if the presumed complication risk of preventive endovascular or neurosurgical intervention is higher than the risk of rupture. Aneurysm wall inflammation and blood pressure are attractive modifiable risk factors of aneurysm rupture and growth. - AIM: To investigate in patients with an unruptured intracranial aneurysm who do not qualify for preventive endovascular or neurosurgical intervention whether a treatment strategy of acetylsalicylic acid 100 mg/day plus intensive blood pressure treatment (targeted systolic blood pressure < 120 mmHg, monitored with a home blood pressure measuring device) reduces the risk of aneurysm rupture or growth compared with care as usual (no acetylsalicylic acid, targeted office systolic blood pressure < 140 mmHg, no home blood pressure measuring device). - SAMPLE SIZE: We aim to randomize 776 patients 1:1 to the intervention arm or care as usual. - DESIGN: Bi-national (Germany and the Netherlands) multicenter, prospective, randomized, open-label phase III trial with blinded outcome assessment. - OUTCOMES: The primary outcome is aneurysm rupture or growth (increase in any aneurysm diameter by ≥ 1 mm) on repeated MR or CT angiography within 36 ± 6 months after randomization. - DISCUSSION: The Prospective Randomized Open-label Trial to Evaluate risk faCTor management in patients with Unruptured intracranial aneurysms (PROTECT-U) is the first randomized trial to investigate if a medical strategy reduces the risk of rupture or growth of intracranial aneurysms in patients not undergoing preventive endovascular or neurosurgical aneurysm treatment. Clinical trial Registration: NCT03063541.
Im Titel ist "factor" geschrieben mit Großbuchstaben bei "C" und "T"
Gesehen am 14.04.2020